1998
DOI: 10.1128/aac.42.10.2595
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Antimicrobial Photochemotherapy

Abstract: This study explores a new approach for antimicrobial therapy with light activation of targeted poly-l-lysine (pL)–chlorine6 (c e6 ) conjugates. The goal was to test the hypothesis that these conjugates between pL and c e6 would efficiently target photodestruction towards gram-positive (Actinomyces viscosus) and gram-negative (Porphyromonas gingivalis) oral species while sparing an oral epithelial cell line (HCPC-1). Conjugates of c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
158
0
9

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(169 citation statements)
references
References 33 publications
2
158
0
9
Order By: Relevance
“…In our previous studies, we have shown that a cationic conjugate between c e6 and a pL chain of 20 amino acids was effective in photoinactivation of the Gramnegative P. gingivalis and the Gram-positive A. naeslundii genospecies 2 [22]. Hamblin et al [38] have recently shown that photoinactivation of E. coli was achieved by a 37-lysine pL-c e6 conjugate at concentrations up to 4 mM c e6 equivalent whereas the concentration of a 8-lysine conjugate needed to be raised to 100 mM c e6 equivalent to kill E. coli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, we have shown that a cationic conjugate between c e6 and a pL chain of 20 amino acids was effective in photoinactivation of the Gramnegative P. gingivalis and the Gram-positive A. naeslundii genospecies 2 [22]. Hamblin et al [38] have recently shown that photoinactivation of E. coli was achieved by a 37-lysine pL-c e6 conjugate at concentrations up to 4 mM c e6 equivalent whereas the concentration of a 8-lysine conjugate needed to be raised to 100 mM c e6 equivalent to kill E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown in vitro that a polycationic conjugate between poly-L-lysine (pL) and the PS chlorin e6 (c e6 ) could efficiently target photodestruction of Gram-negative (Porphyromonas gingivalis) and Gram-positive (Actinomyces naeslundii, formerly Actinomyces viscosus) oral species while sparing an oral epithelial cell line [22]. We have also shown that a single photomechanical wave (PW) generated by a Q-switched laser induced a 75% increase in the penetration depth of the cationic PS methylene blue into a population of A. naeslundii genospecies 2 43146 growing in vitro on bovine enamel surfaces [23].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that oral bacteria in planktonic cultures and in plaque scrapings are susceptible to antimicrobial photodynamic therapy [77][78][79][80][81]. Moreover, recent studies have reported that photodynamic therapy induced bacterial cell killing and reduced bacterial numbers by more than tenfold in S. mutans, Streptococcus sobrinus, and Streptococcus sanguinis biofilms when toluidine blue O or erythrosine was used as the photosensitizer [82][83][84][85].…”
Section: Antimicrobial Photodynamic Therapy and Periodontologymentioning
confidence: 97%
“…In PDT, ROS generated by an illuminated photosensitizer introduced exogenously into the bacteria induce a toxic effect [32][33][34]. This photochemical treatment has been used successfully in vitro [7].…”
Section: Discussionmentioning
confidence: 99%